ATRAKSI WISATA RELIGI DI MASJID SYAHBUDDIN KABUPATEN SIAK PROVINSI RIAU - Abdul Sidiq; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aimed to investigated religious tourist attraction. Which is a tourist attraction the attractiveness of an attraction so that the tourist interested in visiting the tourist attraction and Also to determine the Syahhabuddin mosque tourist activities in Siak district of Riau province. This study used descriptive qualitative method which describe situation in accordance with the event, the sourcer is the head daily Syahhabuddin mosque and Disparpora Siak district. The result of this study are Syahhabuddin mosque religious tourist attraction showed the historical mosque, the unique architecture , and the adjacent mosque location to the river and Sultan Syarif Khasim II tombs. While the tourist activities in Syahhabuddin mosque itself are prayer, pilgrimage while enjoying the beauty of the Siak river view and following recitation. The study expected to increase knowledge about Syahbuddin mosque as religious tourist attraction, and as consideration for the Syahhabuddin mosque tourism to increase the tourists number enjoyed it. Keyword : Religious tourist attraction , Syahhabuddin mosque